1998
DOI: 10.1070/pu1998v041n10abeh000463
|View full text |Cite
|
Sign up to set email alerts
|

Realization of discrete states during fluctuations in macroscopic processes

Abstract: It is shown that due to fluctuations, a sequence of discrete values is generated by successive measurement events whatever the type of the process measured. The corresponding histograms have much the same shape at any given time and for processes of a different nature and are very likely to change shape simultaneously for various processes and in widely distant laboratories. For a series of successive histograms, any given one is highly probably similar to its nearest neighbors and occurs repeatedly with a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 1 publication
6
35
0
Order By: Relevance
“…While it is possible to attribute the annual periods to a ''seasonal'' influence with a clear annual variation, such as temperature, periodicities on the order of six months, one month, or less, are not. Furthermore, as shown in Sturrock et al (2010a,b), Sturrock et al (2011a), Shnoll et al (1998) and Veprev and Muromtsev (2012), the observed decay frequencies align closely with known solar periodicites. This tends to support the original hypotheses of , suggesting that there is a solar influence on radioactive decay rates on Earth.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…While it is possible to attribute the annual periods to a ''seasonal'' influence with a clear annual variation, such as temperature, periodicities on the order of six months, one month, or less, are not. Furthermore, as shown in Sturrock et al (2010a,b), Sturrock et al (2011a), Shnoll et al (1998) and Veprev and Muromtsev (2012), the observed decay frequencies align closely with known solar periodicites. This tends to support the original hypotheses of , suggesting that there is a solar influence on radioactive decay rates on Earth.…”
Section: Discussionsupporting
confidence: 59%
“…This could lead to a determination of the cause of the non-random behavior exhibited by the decays of some isotopes, which should eventually lead to an understanding of the governing mechanism. Shnoll et al (1998) Shnoll et al (1998) a Only the count rate ratio data were available.…”
Section: Discussionmentioning
confidence: 99%
“…Processes such as the chemical reactions, radiative decay, and others should reflect the structures of the system emitter and processes of its formation. This can apparently be explained by the fine nature of the distributions presented in many pub lications associated with the description of the phe nomena first mentioned by Shnol' [11].…”
mentioning
confidence: 95%
“…4. The variation in the "heavy tail" probability can be found by multi plying the starting dependence of the probability or its "tail" by the factor of increasing probability F i (11). Modulation of the "easy tail" of the standard distribu tion by multiplying by factor F i allows us to acquire the actual pattern of origination of rare events in a natural manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation